Career Development as a Mediator of Internal Communication and Work Motivation on Employee Performance - Wati, Aslinda; Paleni, Herman; Sardiyo, Sardiyo (Universitas Bangka Belitung, 2025)
This study examines how internal communication and work motivation affect civil servant performance through career development as a mediator. Using a quantitative approach with an explanatory design to describe the relationship and influence between variables on 31 civil servants in the Communication, Informatics, and Statistics Office of Musi Rawas Regency, data were collected through questionnaires, observation, and documentation. The analysis included linear regression, path analysis, and Sobel's test to examine direct and indirect effects. The results showed that internal communication and work motivation had a positive effect on career development and performance; career development significantly mediated the influence of internal communication and work motivation on employee performance. These findings emphasize the importance of career-based intervention designs that link organizational communication practices and employee motivation to performance achievement. The uniqueness of the study lies in testing the mediation model at the district level with explicit links between individual/organizational and performance, providing a concise and measurable empirical basis for formulating human resource development policies in the public sector. Recommendations emphasize strengthening internal communication, maintaining motivation, and structured career development programs to optimize civil servant performance.